A SOCIOLINGUISTIC FACTOR ANALYSIS OF YORUBA-ENGLISH BILINGUALISM AMONG FORM V PUPILS IN SECONDARY GRAMMAR SCHOOLS IN THE IBADAN AREA (1977)
This study regards certain variable sociological and educational factors as determinants of a person's or a group's degree of bilingualism, and attempts to ascertain their role in the proficiency abilities of Yoruba-English bilinguals in the fifth form of the secondary grammar school. In Chapter I is an outline of the development of scholastic interest in the curious phenomenon of bilingualism. Some of the theories and research approaches to the study of bilingualism are explicated. The chapter concludes by indicating the descriptive sociolinguistic approach adopted for the study. Chapter II examines the relative role and Status of Yoruba and English among the Yoruba people in the colonial era and in Contemporary Nigeria. The Information and analysis in the chapter constitute a background against which proficiency attainments in the two languages may be understood. Chapter III is methodological. Certain assumptions as well as the objectives of the study are stated. A number of hypotheses of Yoruba-English bilingual proficiency are postulated and the procedure for verifying them described. This involves the use of a language background questionnaire, and tests of language proficiency. In Chapters IV to VI the hypotheses are tested by matching the achievements of the subjects in the tests of proficiency with specific items in the language background information which have been hypothesized as determinants of proficiency. The hypotheses tested in chapter IV deal with bilingual comprehension, in Chapter V with bilingual fluency, and in Chapter VI with bilingual choice and usage habits. In each case the results are stated and discussed. In the last chapter (Chapter VII) we overview the whole investigation, summarising the major findings as regards the nature of bilingual proficiency, and assessing the effectiveness of the instruments used in the investigation. We also consider some of the social implications of the differences in English achievements among subgroups in the category of bilinguals studied, and make some suggestions for avoiding their undesirable possible consequences. Finally, four of the sociolinguistic problems which bilingualism poses are suggested for future investigation.